General geology and study of iron oxide in Temangan - Nur Aina Anoar (2017)
This study is about the general geology and study of iron oxide in Temangan district in Kelantan with coordinate of latitude ranges from 05° 39’ 30” N to 05° 42’ 00” N and longitude from 102° 09’ 30” E to 102° 11’ 30” E. The purpose of this study is to produce a geological map of the study area and studying the physical and chemical properties of iron oxide within the study area. Field observation and mapping at the study area have been done accordingly. Five rock samples were collected within the study area for petrography studies. The study area was made up of Permian to Jurassic of Gua Musang Formation with the intermediate igneous rocks and ignimbrite. Three samples that contained iron oxide minerals were analysed using X-Ray Diffraction and X-Ray Fluoresence techniques for physical and chemical properties. From the XRD analysis, the three samples have shown the similar graph patterns compatible with value of the highest peak. Based on the result of X-Ray Fluoresence, it was cleared that the concentration of the elements in each sample is controlled by the structural and geomorphological setting of the locality specifically for the composition of iron oxide (Fe2o3 ).